Leadership reflections a year on from the rapid roll-out of virtual clinics due to COVID-19: a commentary. Issue 3 (26th May 2021) - Gilbert, Anthony W; Davies, Lucy; Doyle, John; Patel, Saroj; Martin, Luke; Jagpal, Deepak; Billany, Joe C T; Bateson, John
Abstract : COVID-19 changed the way we delivered care to our patients at our Hospital. Prior to the pandemic, no patient facing video clinics and only a small number of telephone clinics were held. In this paper, we share our experience of rapidly implementing virtual clinics (VCs) due to COVID-19. This commentary is based on focused discussions between hospital leaders and provides a reflective account and commentary on leadership lessons learnt from our experience of deploying VCs. We outline success factors (being able to capitalise on existing strategy, having time and space to establish VCs, using an agreed improvement framework, empowering a diverse and expert implementation team with a flat hierarchy, using efficient decision pathways, communication and staff willingness to change), technical challenges (patient capability and skills to use technology, patient connectivity and platform capacity) and considerations for the future (sustaining new ways of working, platform selection, integration, business continuity and commissioning considerations, barriers regarding capability and communication, effectiveness and clinical outcomes). Finally, we provide an overview of the leadership lessons from this project and identify key areas of focus for delivering successful change projects in future (the vision, allocation of resources, methodology selection and managing the skills gap).